Resolving the Mark-to Market vs Historical Cost debate: where do we go from here? - Chatham, Michael; Kopf, Jerry (Archives of Business Research, 2020)
Mark-to-market accounting has been one of the most hotly debated changes in accounting. Some, including the past Federal Reserve Chairman, Ben Bernanke, cited it as one of the causes of the 2007-2008 U.S. economic crisis. Many in the accounting community disagree with the Chairman and feel that movement away from historical cost has been a positive for transparency. Though countless individuals have voiced either their opposition or their support of mark-to-market accounting, each of them seems to view the debate as one between either historical cost or mark-to-market. After reviewing the arguments for both historical cost and mark-to-market in detail, we conclude the production of two financial statements, a traditional Balance Sheet based on historical costs, and a Statement of Financial Condition based on mark-to-market, would be relatively inexpensive to produce and would better provide the information needed by different users employing said financial information for, invariably, different purposes.